Content Analysis of Sakinah Family Values in Ustadz Hanan Attaki's YouTube Da'wah Content: English - Muhammad Syarqawi A Nasution; Khatibah (Jurnal Komunikasi dan Ilmu Sosial, 2026)
The increasing divorce rate in Indonesia underscores the urgent need to strengthen sakinah family values through digital da'wah media. Although YouTube has been widely utilized as a platform for Islamic preaching, studies examining how sakinah family values are constructed within digital da'wah content remain limited. This study aims to analyze the da'wah messages related to the sakinah family and to identify how these values are constructed in Ustadz Hanan Attaki's YouTube content. This research employed a qualitative approach using content analysis of a purposively selected YouTube video with a duration of 18 minutes and 49 seconds, chosen because it specifically discusses the dynamics of a sakinah family and the strengthening of marital relationships. The unit of analysis consisted of segments of da'wah messages, which were categorized according to sakinah family values. The findings reveal that communication and empathy constitute the primary foundation for strengthening marital relationships, which in turn foster greater family responsibility. These values further contribute to family resilience through the reinforcement of spirituality, patience, the ability to derive wisdom from life’s challenges, and a balanced distribution of roles between husband and wife. Family responsibility, along with communication and empathy, emerged as the most dominant themes in the analyzed da'wah content. The construction of these values is conveyed through inspirational stories, relatable illustrations drawn from everyday family life, and practical solutions to common household challenges. These findings suggest that YouTube serves as an effective medium for digital da'wah in constructing and reinforcing sakinah family values, making it a relevant platform for promoting family harmony in contemporary society.